2013
DOI: 10.1093/jac/dkt486
|View full text |Cite
|
Sign up to set email alerts
|

Rapid kill of malaria parasites by artemisinin and semi-synthetic endoperoxides involves ROS-dependent depolarization of the membrane potential

Abstract: ObjectivesArtemisinin and artemisinin semi-synthetic derivatives (collectively known as endoperoxides) are first-line antimalarials for the treatment of uncomplicated and severe malaria. Endoperoxides display very fast killing rates and are generally recalcitrant to parasite resistance development. These key pharmacodynamic features are a result of a complex mechanism of action, the details of which lack consensus. Here, we report on the primary physiological events leading to parasite death.MethodsParasite mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 72 publications
(112 reference statements)
6
106
0
1
Order By: Relevance
“…In the parasite, a V-type ATPase generates a proton motive force across the parasite plasma membrane as well as across the digestive food vacuole (49,50). It has previously been shown that ART results in rapid depolarization of the parasite plasma membrane (51). Although the depolarization of the plasma membrane was previously shown to be partially attributed to lipid peroxidation, the ARTABPPs data presented here could be interpreted as showing the potential for a direct inhibition of the V-type ATPase activity by ART.…”
Section: Resultsmentioning
confidence: 99%
“…In the parasite, a V-type ATPase generates a proton motive force across the parasite plasma membrane as well as across the digestive food vacuole (49,50). It has previously been shown that ART results in rapid depolarization of the parasite plasma membrane (51). Although the depolarization of the plasma membrane was previously shown to be partially attributed to lipid peroxidation, the ARTABPPs data presented here could be interpreted as showing the potential for a direct inhibition of the V-type ATPase activity by ART.…”
Section: Resultsmentioning
confidence: 99%
“…Bioactivated endoperoxides have been shown to generate downstream radical oxygen species, disrupting a number of parasite membranes and enzymes (23). In cancer cells, cytotoxic activity has been shown to arise from ROS-mediated oxidative DNA damage induced by ART (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, artemisinins have been shown to be distributed to the mitochondrial compartment in the parasite, result-ing in impaired mitochondrial functions (22) and ROS-dependent depolarization of plasma and mitochondrial membranes (23). Even though many cellular targets have been identified, the mechanism of action of artemisinin derivatives still remains ambiguous.…”
mentioning
confidence: 99%
“…Characterization of the mode of action of allelochemicals in receptor species is essential for a full understanding of this planteplant interaction. Previous studies demonstrated that allelochemicals could have multiple phytotoxic effects to influence almost every aspect of plant growth and development such as gene expression, phytohormone activity, ion uptake and photosynthetic function (Babula et al, 2009). Therefore, phytotoxic mechanisms of allelochemicals will undoubtedly be complex.…”
Section: Introductionmentioning
confidence: 99%